2022
DOI: 10.5937/bjdm2201015p
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of working length measurement by Raypex 6: Electronic apex locator versus actual measurements under stereomicroscope

Abstract: Background/Aim: This study aimed to evaluate the precision of the Raypex 6 apex locator in locating the apical constriction (AC) and major foramen (MF) during a root canal treatment compared with a microscopic evaluation. Another aim of the present study was to evaluate the accuracy of the Raypex 6 in the presence of different irrigating solutions (NaOCl, saline, EDTA, etidronic acid-HEBP). Material and Methods: One hundred and nine patients were included in this study and were randomly assigned into four grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Nahidi et al [ 15 ] found no significant difference in the WL measured by Root ZX and the actual WL in single canal maxillary incisors. Although it has been reported that Root ZX overestimates the WL, it should be mentioned that the margin of error within 1 mm is clinically acceptable because evidence shows that apical constriction is located within this range [ 17 , 19 , 20 , 21 ]. Difference in the results of the two studies may be due to differences in sample size, type of tooth, and method of measurement of the actual WL (use of histological sections in the study by Nahidi et al [ 15 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Nahidi et al [ 15 ] found no significant difference in the WL measured by Root ZX and the actual WL in single canal maxillary incisors. Although it has been reported that Root ZX overestimates the WL, it should be mentioned that the margin of error within 1 mm is clinically acceptable because evidence shows that apical constriction is located within this range [ 17 , 19 , 20 , 21 ]. Difference in the results of the two studies may be due to differences in sample size, type of tooth, and method of measurement of the actual WL (use of histological sections in the study by Nahidi et al [ 15 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The most popular system is the third-generation apex locator. 9 It uses two frequencies and measures the difference between them; however, the type of moisture present may affect reading accuracy. 9,10 On the other hand, the 4 th generation uses five frequencies, but they make mathematical measurements rather than measurements according to a database.…”
Section: Introductionmentioning
confidence: 99%
“…9 It uses two frequencies and measures the difference between them; however, the type of moisture present may affect reading accuracy. 9,10 On the other hand, the 4 th generation uses five frequencies, but they make mathematical measurements rather than measurements according to a database. 9,10 However, there are no marked differences in reading accuracy between older apex locator generations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations